PERAN DINAS PERTANIAN DALAM UPAYA PENGENDALIAN INFLASI CABAI - Nursanti Nursanti; Nurmadhani Fitri Suyuthi; Abdul Majid Bakri (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the managerial role of Dinas Pertanian of Penajam Paser Utara Regency in efforts to control chili inflation in Penajam District and to identify the supporting and inhibiting factors affecting its implementation. Controlling chili inflation is an important effort to maintain food price stability and ensure the availability of chili commodities for the community. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The research informants consisted of Dinas Pertanian, Penyuluh Pertanian Lapangan (PPL), farmer groups, and chili farmers. Data were analyzed using which includes the functions of planning, organizing, actuating and controlling.The results indicate that Dinas Pertanian of Penajam Paser Utara Regency has implemented management functions in controlling chili inflation effectively through various programs aimed at increasing production and stabilizing chili supply. The obstacles encountered include extreme weather conditions, pest and plant disease outbreaks, high production costs, fluctuations in chili prices, and dependence on supplies from outside the region. Meanwhile, the supporting factors include support from local government programs, the active role of Penyuluh Pertanian Lapangan (PPL), active farmer groups, support from Tim Pengendalian Inflasi Daerah (TPID), and the growing potential of local chili production.